Prognostic value of various subtypes of extracellular DNA in ovarian cancer patients - Katarina Kalavska; Tomas Minarik; Barbora Vlkova; Denisa Manasova; Michaela Kubickova; Andrej Jurik; Jozef Mardiak; Jozef Sufliarsky; Peter Celec; Michal Mego (BMC, 2018)
Abstract Background Patients with ovarian cancer represent a heterogeneous population with a variable prognosis and response to chemotherapy. Plasma DNA has been shown to have a prognostic value in different types of cancer including ovarian carcinoma. Whether total circulating DNA, which can be assessed much easier without knowing the tumor-specific mutations, has similar informative value is currently unknown. The aim of this study was to evaluate the prognostic value of extracellular DNA in advanced ovarian cancer. Methods This prospective study included 67 patients (pts) with ovarian cancer treated with 1st line paclitaxel and carboplatin (25 pts) and paclitaxel, carboplatin and bevacizumab (42 pts). Thirty-five patients had optimal surgical debulking before chemotherapy. Extracellular DNA was quantified using real time PCR before administration of chemotherapy (67 pts) and after 6 cycles of chemotherapy (44 pts). Results Total extracellular DNA (ecDNA), as well as extracellular DNA of nuclear (nDNA) and mitochondrial origin (mtDNA) significantly (p < 0.05) decreased after 6 cycles of chemotherapy (by 54%, 63% and 52%, respectively. Patients with stage I disease had significantly lower mtDNA compared to patients with stage II-IV (8604 vs. 16, 984 ge/mL, p = 0.03). Patients with lower baseline nDNA had superior progression-free (HR = 0.35 (0.14-0.86)) and overall survival (HR = 0.18 (0.04-0.77). The prognostic value of nDNA was confirmed independent of tumor stage and confirmed in multivariate analysis. Conclusions Our data suggest that ecDNA of both, nuclear and mitochondrial origin could be added to prognostic markers in ovarian cancer. Analysis of ecDNA does not require the knowledge of tumor-specific mutations in contrast to the quantification of tumor-derived ecDNA. Study of the dynamics and cell type-specific source of the ecDNA could shed light on its biology in cancer and might help to direct the treatment of ovarian cancer.